PENGARUH RASIO LIKUIDITAS, LEVERAGE, OPERATING CAPACITY, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS - Widhiari, Ni Luh Made Ayu; Aryani Merkusiwati, Ni Ketut Lely (E-Jurnal Akuntansi; Vol 11 No 2 (2015), 2015)
Financial distress is a phase of decline in financial condition that occurred before the onset of bankruptcy. This study aims to examine the effect of liquidity, leverage, operating capacity, and sales growth of financial distress. This research was conducted at the companies listed on the Stock Exchange in 2010-2013. The samples used were as many as 152 observations selected using purposive sampling method. Data collection was done by using the documentation obtained from BEI website and ICMD . The analysis technique used is logistic regression. The results of the analysis of this study indicate that the liquidity, the operating capacity, and sales growth ratios are able to affects the financial distress of manufacturing company with negative direction. While the leverage ratio are not able to influence the probability of financial distress.
Keywords: financial distress, financial ratios